P264 A multi-centre review of the management of pulmonary Non-Tuberculous Mycobacterial (NTM) infection in HIV-negative subjects. (12th November 2015) - Rawson, TM; Abbara, A; Kranzer, K; Ritchie, A; Milburn, J; Brown, T; Adeboyeku, D; Buckley, J; Davidson, RN; Berry, M; Kon, OM; John, L
Abstract : Introduction: Non-Tuberculous Mycobacteria (NTM) are ubiquitous in the environment meaning clinical, radiological and microbiological criteria are important in diagnosing NTM lung disease. A multicentre, retrospective review was performed to characterise NTM disease within our region and describe the outcomes of current management. Methods: All NTM positive sputum samples received by the National Mycobacterium Reference Laboratory (NMRL) from Imperial College NHS Healthcare and North West London Hospitals NHS Trusts between 2010–2014 were extracted. HIV-negative individuals with ≥2 positive sputum samples or ≥1 positive bronchoalveolar lavage were included. Demographic, clinical, radiological, microbiological, management and outcome data was obtained from electronic records. Results: 1190 NTM sputum samples were identified from 822 individuals. 152 individual patients met inclusion criteria for analysis. Table 1 describes cohort demographics. Within the cohort 48/152 (32%) were treated for NTM disease. All treated subjects and 74/104 (71%) non-treated subjects met international guidelines for diagnosis of NTM infection, which included positive clinical, radiological (cavities or bronchiectasis +/- nodules or infiltrates) and microbiological criteria. Mycobacterium avium complex (MAC) was the most commonly isolated (68/152; 45%) and treated organism (21/48; 44%) followed by Mycobacterium kansasii (11/48; 23%). 19/48 (40%) completed treatment (median duration: 17 months [IQR: 12–24]). 10/48 (21%) remain on treatment (median duration: 18 months [IQR: 11–36]), 11/48 (23%) stopped treatment due to side effects and 13/48 (27%) were either lost to follow up or treated for Mycobacterium tuberculosis . Of those treated, 29/48 (60%) culture converted; 23/29 (79%) remain negative at 12 months post culture conversion. Of 19/48 who completed treatment, 5/19 (26%) had symptomatic or radiological disease progression compared to 11/28 (39%) who did not complete treatment. 11/48 (23%) patients died within the treatment group. Within the untreated subjects who met international guidelines for NTM infection (74/104), mortality was 19/74 (26%) (p = 0.83). Discussion: NTM is a challenging disease with only 39% of eligible subjects receiving treatment and a high associated mortality. Furthermore, only 40% starting treatment completed it and the 21% who remain on treatment have been treated for a median duration of 18 months to date. Unlike similar HIV-negative UK cohorts, MAC pulmonary disease is the most prevalent.